Waiting in Joyful Hope : Daily Reflections for Advent and Christmas 2016-17 - Morneau, Robert F. (Book collections on Project MUSE., 2016)
Prepare spiritually for the coming of Christ with this popular, easy-to-use annual guide. During the especially busy Advent and Christmas seasons, this book offers brief, down-to-earth reflections that bring prayer and Scripture into everyday life in a thought-provoking and lasting way. Through Bishop Robert Morneau's insightful reflections on Scripture readings from the daily Mass, readers will grow in their understanding of the word of God. This book will help busy people achieve their goal of enriching their personal prayer life during the seasons of Advent and Christmas.